Audit Delay Pada Sektor Perbankan Di Indonesia - Dela Sasmita, Anggi; Sari, Egi Gumala (JURNAL AKUNTANSI DAN AUDIT TRI BHAKTI, 2024)
Purpose – This research aims to determine the effect of company size andprofitability on audit delay.Design/methodology/approach – This research uses quantitative data, thesample in this research is banking sub-sector companies listed on theIndonesia Stock Exchange for the period 2018 - 2022, totaling 27 companies.The analysis technique used to test the hypothesis is multiple regressionanalysis using Eviews 9 software.Findings – The research results show that the Company Size variable has anegative and statistically significant effect on audit delay, the Profitabilityvariable has a negative and statistically significant effect on audit delay.Originality/value - This research discusses Audit Delay and other factorssuch as Company Size and Profitability which focuses on banking sub-sectorcompanies.